Anti-Cyclic Citrullinated Peptide Antibodies in Rheumatoid Arthritis and Their Relationship with Extra-Articular Manifestations - Özgür ORTANCIL,; Nercivan BULMUŞ,; Şenay ÖZDOLAP,; Sibel KIRAN,; Mehmet ARASLI3, (Archives of Rheumatology, 2011)
Objectives: In this study, we investigated the relationship between extra-articular manifestations (EAM) and anti-cyclic citrullinated peptide (anti-CCP) antibodies. Patients and methods: Sixty-seven p atients ( 53 f emales, 1 4 males; mean age 57.4±13.5 years; range 26 to 82 years) diagnosed with rheumatoid arthritis (RA) according to the ACR (American College of Rheumatology) criteria between January 2009 - December 2009 were included in the study. The age, gender, disease duration, and EAMs (rheumatoid nodules, pulmonary nodules, pulmonary fibrosis, keratoconjunctivitis sicca) of each patient were recorded, and the anti-CCP antibody and rheumatoid factor (RF) positivity and serum RF levels were evaluated. Results: Extra-articular manifestations were present in 28 (41.8%) of the patients. Anti-CCP antibodies were present in 34 (50.7%) patients. Positivity of anti-CCP antibodies was found in 16 (57.1%) patients with EAM compared to 18 (46.2%) patients without EAM (p>0.05). Rheumatoid factor positivity was found in 23 (82.1%) patients with EAM compared with 30 (76.9%) patients without EAM (p>0.05). The serum levels of RF were 176.5±201.7 IU/ml in the patients with EAM, and 114.1±144.8 IU/ml in the patients without EAM (p>0.05). The mean serum titers of RF were significantly higher in the patients with pulmonary fibrosis than in those without pulmonary fibrosis (237.8±204.8 IU/ml and 118.9±158.6 IU/ml respectively; p=0.036). Conclusion: It is known that EAMs increase morbidity and mortality in patients with rheumatoid arthritis. Thus, the markers that help identify patients with severe disease have an important role in making a decision for early aggressive treatment. Studies that investigate the relationship between anti-CCP antibodies and EAM have conflicting results. In this study, no relationship was found between the antibodies against citrullinated peptides and the presence of EAMs. We think that further studies with a larger sample size are necessary to evaluate the relationship between EAM and anti-CCP antibodies.